Assessment of Forest Health in Various Forest Types in Lampung Province - Safe'i, Rahmat; Wulandari, Christine; Kaskoyo, Hari (Jurnal Sylva Lestari, 2019)
In Lampung Province, awareness of the importance of forest health in achieving sustainable forest management in various types of forests is still low so that forest health problems have not received serious attention so far. This study aims to obtain indicators of forest health assessment and the status of forest health conditions in various types of forests in Lampung Province. This research was carried out in mangrove and community forests in East Lampung District, and protected and conservation forests in Tanggamus District in 2018. The stages of this study consisted of formulating guarantees of forest health indicators, making measuring plots, measuring forest health, processing data, and forest health assessment. The results showed that indicators for assessing the health of forests in mangrove forests are vitality and biodiversity, in community forests are productivity, vitality and site quality, in protected forests are biodiversity, vitality and productivity, and in conservation forests are biodiversity and productivity. The status of health conditions in each cluster of plots in mangrove forest is bad and good, in community forests is good and medium, in protected forests is bad and good, and in conservation forests are bad and good. Keywords: indicator, forest health status, forest types, Lampung Province